2009
DOI: 10.1007/s00264-009-0864-4
|View full text |Cite
|
Sign up to set email alerts
|

Objective assessments of medial osteoarthritic knee severity by MRI: new computer software to evaluate femoral condyle contours

Abstract: An irregular contour of the medial femoral condyle (MFC) on magnetic resonance imaging (MRI) appears to indicate the severity of medial-type knee osteoarthritis (OA). The purpose of this study was to establish a system to enable objective assessments of OA knee severity using newly developed software that semiautomatically measures irregularity of the MFC. (1) We evaluated 48 patients aged 50-83 years with 55 knees of medial-type OA. The following scores were recorded: Lysholm score, visual analogue scale (VAS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“… NA High (71) Torres 2006 [ 103 ] MRI attrition, (WORMS) TFJ and PFJ (C) Pain VAS (C) Nil Coefficient 3.33, 95 % CI 1.79 to 4.87 Coefficient 1.91, 95 % CI 0.68 to 3.13 + High (68) MRI bone attrition - case−control studies Javaid 2012 [ 139 ] Baseline semi-quantitative MRI attrition size (WORMS) (C) TFJ and PFJ Presence of frequent knee pain (C) after 2 years Nil OR 2.40, 95 % CI 1.51 to 3.83 NR + Low (59) MRI bone shape/dimension - cohort studies Everhart 2014 [ 114 ] Baseline TFJ subchondral surface ratio of medial and lateral TFJ compartments (C) Incident frequent knee pain at 48 months, (L) Sex, race, age, BMI, tobacco use, activity level, knee coronal alignment, baseline symptoms, injury history, surgery history, KL grade, and JSW NR Medial SSR OR 0.48, 95 % CI 0.30 to 0.75, p = 0.0009. Lateral SSR OR 1.27, 95 % CI 0.86 to 1.88, p = 0.19 - larger MSSR gets less incident frequent knee pain High (61) MRI bone shape/dimension - cross-sectional studies Ochiai 2010 [ 47 ] MRI irregularity of femoral condyle contour (C) Knee pain VAS (C) Nil Irregularity of femoral condyle contour r = 0.472, p = 0.0021 NR + Low (50) MRI bone cyst - cohort studies Sowers 2011 [ 28 ] Semi-quantitative MRI bone cyst size in TFJ (C) Increasing WOMAC pain (L) Nil NR NR analysis described as not significant but data not shown NA Low (53) MRI bone cyst - cross-sectional studies Kornaat 2006 [ 130 ] Semi-quantitative MRI bone cyst(C) Chronic pain presence (C) Nil NR Patellofemoral OR 1.83, 95 % CI (0.80 to 4.16) NA H...…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… NA High (71) Torres 2006 [ 103 ] MRI attrition, (WORMS) TFJ and PFJ (C) Pain VAS (C) Nil Coefficient 3.33, 95 % CI 1.79 to 4.87 Coefficient 1.91, 95 % CI 0.68 to 3.13 + High (68) MRI bone attrition - case−control studies Javaid 2012 [ 139 ] Baseline semi-quantitative MRI attrition size (WORMS) (C) TFJ and PFJ Presence of frequent knee pain (C) after 2 years Nil OR 2.40, 95 % CI 1.51 to 3.83 NR + Low (59) MRI bone shape/dimension - cohort studies Everhart 2014 [ 114 ] Baseline TFJ subchondral surface ratio of medial and lateral TFJ compartments (C) Incident frequent knee pain at 48 months, (L) Sex, race, age, BMI, tobacco use, activity level, knee coronal alignment, baseline symptoms, injury history, surgery history, KL grade, and JSW NR Medial SSR OR 0.48, 95 % CI 0.30 to 0.75, p = 0.0009. Lateral SSR OR 1.27, 95 % CI 0.86 to 1.88, p = 0.19 - larger MSSR gets less incident frequent knee pain High (61) MRI bone shape/dimension - cross-sectional studies Ochiai 2010 [ 47 ] MRI irregularity of femoral condyle contour (C) Knee pain VAS (C) Nil Irregularity of femoral condyle contour r = 0.472, p = 0.0021 NR + Low (50) MRI bone cyst - cohort studies Sowers 2011 [ 28 ] Semi-quantitative MRI bone cyst size in TFJ (C) Increasing WOMAC pain (L) Nil NR NR analysis described as not significant but data not shown NA Low (53) MRI bone cyst - cross-sectional studies Kornaat 2006 [ 130 ] Semi-quantitative MRI bone cyst(C) Chronic pain presence (C) Nil NR Patellofemoral OR 1.83, 95 % CI (0.80 to 4.16) NA H...…”
Section: Resultsmentioning
confidence: 99%
“…MRI (one cohort, one cross-sectional study): one prospective, well-adjusted, high quality analysis found the femoro-tibial articulating surface mismatch was associated with incident frequent knee pain [ 114 ]. One unadjusted cross-sectional analysis found the irregularity of the femoral condyle surface was associated with severity of knee pain [ 47 ]. In summary, specific features of bone shape are independently associated with incident frequent knee pain and severity of pain.…”
Section: Resultsmentioning
confidence: 99%
“…This study analyzed the relation between the medial knee contact force during the stance phase and knee pain and dysfunction in elderly subjects, using musculoskeletal simulation analysis and a self-reported knee function measure JKOM to have context of life style for Japanese elderly. The total JKOM score was reported to be 50−60 for patients with mild and moderate osteoarthritis (Kellgren and Lawrence grade I and II) 21,22) . The median total JKOM score for our pain group subjects was 7.5 (range, 1−37); therefore, they had very mild knee dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…Since MRI images depicting bone are known to be accurately related to the macroscopic appearance of denuded bone (Cohen et al ., ; Iwaki et al ., ; Woodhead et al ., ; Leitzes et al ., ; Louis et al ., ; Ochiai et al ., ), a grading system that is equally applicable to clinical and archaeological skeletal populations was developed. This new system, the Clinical Archeological Osteoarthritis Scale (CAOS), was used to grade the degree of knee OA visible in MRIs and focused on features previously identified as significant in the Kellgren & Lawrence () and Rogers et al .…”
Section: Methodsmentioning
confidence: 99%